Strategi Guru dalam Mengatasi Perilaku Bullying di Lingkungan Sekolah Dasar - Zahwa Dwi Laila Pondaag; Sukmana Sukmana; Seswita Usman; Nurdina Yanti Datuela; Monica Antadi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2026)
Bullying remains a significant issue in elementary schools and has the potential to hinder students' academic and psychosocial development. Bullying behavior can take various forms, including physical, verbal, social, and psychological aggression, which may negatively affect children's self-confidence, learning motivation, and mental health. This article aims to analyze teachers' strategies in addressing Bullying behavior in elementary school settings through a literature review approach. The study employed a descriptive qualitative method using library research. Data were collected from books, accredited national journal articles, educational reports, and previous studies relevant to Bullying in elementary schools. Data analysis was conducted through identification, classification, interpretation, and synthesis of findings from various sources. The results indicate that teachers' strategies in addressing Bullying can be categorized into three main   approaches: preventive strategies through character education and positive school culture, curative strategies through counseling and conflict mediation, and collaborative strategies involving parents and professional support services. These approaches complement each other in creating a safe, supportive, and conducive learning environment for students.